Prinsip Keadilan dan Kebebasan dalam Pemikiran Ekonomi M. Umer Chapra - Hutagaluh, Oskar; Muin, Rahmawati (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research was motivated by researchers' interest in the figure of Umer Chapra as one of the leading figures in Islamic economics and finance. One of Chapra's deep and critical ideas is about usury or bank interest which he put into a small book entitled